Analysis of females' preferences for buttock shapes with different ethnic backgrounds. Issue 5 (5th September 2016) - Yao, Xiaofeng; Wang, Jianping; Ashdown, Susan P.; Luo, Shunhua; Shi, Hui
Abstract : Purpose: Understanding costumer requirements is a precondition for clothing design and manufacturing. A good shapewear designer should know women's preferences for their buttock shapes before making patterns. The purpose of this paper is to figure out factors affecting the beauty of women's buttock shapes and the effect of ethnic background to buttock shapes preference. Design/methodology/approach: The approach utilized both 3D virtual models and 3D printed models to detect women's preference for their buttock shapes. As a first stage, a two-step K -means cluster method was used to classify female buttock shapes into ten groups and these ten kinds of buttock shapes were output as 3D virtual models and printed out as 3D plastic models. In a subsequent stage, 51 Caucasians, 35 African-Americans and 49 Asians were selected to rank the models separately based on their preference and choose the factors which they thought could influence the beauty of buttock shapes. Kendall's W coefficient was tested to help assessing the ranking results. Finally, a sample girdle was designed based on the buttock shape preferences of Asian females as an example, and was tested by a model. Findings: Results showed some correlation between ethnicity and buttock shape preference. Both methods of presentation of the shapes were equally preferred by participants. Caucasian women preferred a full, round buttock shape, which was coordinated to other parts of the body. The attractive buttock shape as judged by Asian women was curvy, not drooping and not too big. African-American women choose buttock shapes that were very full with high buttock bumps as beautiful. A sample girdle was made based on the preferences of Asian females and it proved to perform well in creating the desired shape during the trial test. Originality/value: Current research in the literature about women's buttock beauty is based on plastic surgeons' experiences. This study provides a novel method to analyze female's preference for their buttock shapes; a method that can also be used for other body parts. The results can also be used as an indicator for underwear designers to improve shapewear pattern designs and for consumers to evaluate the shaping ability of shapewear.